Self-Assessment the Competence of the Anesthesia Personnel in Kashan, Iran, and Its Related Factors - Samira Mahmoudi; Akram Yazdani; Fakhrosadat Mirhosseini; Fatemeh Hasan Shiri (Iran University of Medical Sciences, 2023)
Background & Aims One of the goals of providing training to the anesthesia care team is to train staff with theoretical and functional abilities to deal with clinical challenges. However, there is a gap between the existing and desired performance levels of personnel in anesthesia procedures. This study aims to assess the competence of anesthesia personnel in Kashan, Iran, and find its related factors. Materials & Methods This descriptive-analytical study was conducted on 95 anesthesia personnel of hospitals in Kashan, Iran, in 2023, who were selected using a census method. The data collection tools were a demographic form and the Anesthesia Nursing Competence Scale. Data were analyzed in SPSS v.22 software using descriptive statistics (frequency, mean, standard deviation), Mann-Whitney U test, Kruskal-Wallis test, Spearman's correlation test, Point-Biserial correlation test, and regression analysis. Results The mean age of the participants was 34.57±10.1 years. The overall competence level of anesthesia personnel was at a high level (84.84±53.11). Their competence had a significant relationship with their sex and marital status (P<0.05). Conclusion The competencee of anesthesia personnel in Kashan is at a high level in all fields, except for the patient's risk care. It is recommended to empower personnel in this area to prevent adverse events and improve the quality of medical services.